Evaluation of the prevalence of adolescent scoliosis and its associated factors in Gansu Province, China: a cross-sectional study - Huang, Jin; Zhang, Haitao; Wen, Jiantao; Liu, Lili; Xu, Shihong; Wang, Xingsheng; Zhang, Chen; Wang, Huaming; Pei, Shengtai; Cui, Xiaojuan; Wang, Juan; Tang, Dezhi; et al. (Frontiers in Public Health, 2024)
Introduction Gansu Province is situated in the northwest region of China, characterized by diverse and complex topography and a rich diversity of ethnic groups. This study aims to explore the prevalence and risk factors of adolescent suspected scoliosis in Gansu Province through a cross-sectional population study. Methods From April 2022 to July 2022, a prospective cross-sectional study was conducted in Baiyin City, Jinchang City, Lanzhou City, Linxia Hui Autonomous Prefecture, and Gannan Tibetan Autonomous Prefecture in Gansu Province. The screening covered 3,118 middle and high school students across 24 institutions, including middle and high schools. Diagnosis of suspected scoliosis was established through visual inspection, the Adams forward bend test, and measurement of trunk rotation angle. Employing a custom-designed questionnaire, demographic data were collected, and the prevalence of suspected scoliosis was calculated. Univariate and multivariate logistic regression analyses were employed to assess factors associated with suspected scoliosis. Results A total of 3,044 participants were ultimately included in the analysis. The overall prevalence of suspected scoliosis was 5.68% in Gansu Province. The peak prevalence for boy is at 14 years (6.70%), while for girl, it is at 15 years (8.75%). Lanzhou City exhibits the highest prevalence rates (boy, 9.82%; girl, 10.16). The results of univariate logistic regression analysis presented that BMI (OR = 0.92, 95% CI: 0.88–0.96), altitude of habitation (1,600 m-2000 m) (OR = 0.50, 95% CI: 0.34–0.73), altitude of habitation (2000 m-3321 m) (OR = 0.58, 95% CI: 0.40–0.83), family medical history (OR = 1.56, 95% CI: 1.02–2.31), and shoulders of unequal height (OR = 1.49, 95% CI: 1.09–2.03) were significantly correlated with suspected scoliosis. The multivariate logistic regression analysis indicated that BMI (OR = 0.91, 95% CI: 0.86–0.95), altitude of habitation (1,600 m-2000 m) (OR = 0.35, 95% CI: 0.23–0.54), altitude of habitation (2000 m-3321 m) (OR = 0.39, 95% CI: 0.24–0.60), family medical history (OR = 1.66, 95% CI:1.08–2.49), and shoulders of unequal height (OR = 1.45, 95% CI:1.06–1.99) were independently associated with suspected scoliosis. Conclusion Low BMI, residence at an altitude of 1,600 m-3321 m, family medical history, and shoulders of unequal height were independently associated with an increased prevalence of suspected scoliosis. It is recommended to promptly screen high-risk adolescents for suspected scoliosis, provide effective preventive and intervention measures.